2016
DOI: 10.1186/s13045-016-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

H2S protects against fatal myelosuppression by promoting the generation of megakaryocytes/platelets

Abstract: BackgroundOur previous pilot studies aimed to examine the role of hydrogen sulfide (H2S) in the generation of endothelial progenitor cells led to an unexpected result, i.e., H2S promoted the differentiation of certain hematopoietic stem/progenitor cells in the bone marrow. This gave rise to an idea that H2S might promote hematopoiesis.MethodsTo test this idea, a mice model of myelosuppression and cultured fetal liver cells were used to examine the role of H2S in hematopoiesis.ResultsH2S promoted the generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Scanning electron microscopy (SEM) was performed as described previously. 42 The cells were fixed with 2.5% glutaraldehyde and 1% osmium tetroxide and then dehydrated with a gradient of ethanol. The cells were then dehydrated in an HCP-2 critical point dryer (Hitachi, Tokyo, Japan) with liquid CO 2 and were finally observed under a Nova Nano 450 scanning electron microscope.…”
Section: Transmission Electron Microscopy and Scanning Electron Micromentioning
confidence: 99%
“…Scanning electron microscopy (SEM) was performed as described previously. 42 The cells were fixed with 2.5% glutaraldehyde and 1% osmium tetroxide and then dehydrated with a gradient of ethanol. The cells were then dehydrated in an HCP-2 critical point dryer (Hitachi, Tokyo, Japan) with liquid CO 2 and were finally observed under a Nova Nano 450 scanning electron microscope.…”
Section: Transmission Electron Microscopy and Scanning Electron Micromentioning
confidence: 99%
“…Actually, H 2 S has been identified as the third gasotransmitter, which is generated in mammalian cells and quickly permeates cell membranes without using specific transporters (Sen, 2017). A number of studies have investigated the role of H 2 S in triggering cell differentiation, and evidence has been presented that this gas can exert both promotive (Liu et al, 2016) and inhibitory activity (Gambari et al, 2014) in cultured cells. This discrepancy is likely related to the bell-shaped or biphasic pharmacological profile of H 2 S. That is, lower levels of H 2 S exert F I G U R E 7 Knockdown of AKT or inhibition of AKT by DATS leads to a decrease of SOX2 expression in ATC cells.…”
Section: Discussionmentioning
confidence: 99%
“…NaHS, another common H 2 S donor, inhibited human osteoclast differentiation by an NRF2-dependent mechanism (Gambari et al, 2014). Other studies revealed that H 2 S might promote hematopoiesis by enhancing the differentiation of certain hematopoietic stem/progenitor cells in the bone marrow (Liu, Zhang, Xu, Chen, & Zhu, 2016). It was shown that physiologic levels of endogenous H 2 S maintain the proliferation and differentiation capacity of human periodontal ligament stem cells (PDLSCs) (Su et al, 2015).…”
mentioning
confidence: 99%
“…Other groups have shown that H2S promoted the differentiation of certain hematopoietic stem/progenitor cells in the bone marrow [96]. This gave rise to an idea that H2S might promote hematopoiesis.…”
Section: Stem Cell and H2s Signalingmentioning
confidence: 99%
“…In fact, H2S promoted the generation of megakaryocytes, increased platelet levels, ameliorate menorrhagia, and improved survival. H2S is a novel promoter for megakaryopoiesis by acting on the TPO receptors but not TPO to generate megakaryocytes/platelets [96]. Moreover, it was shown that in several cell types, including human inducible pluripotent stem cell (hiPSC)-derived neurons, H2S inhibited complex IV of the mitochondrial respiratory chain and induced apoptosis [97].…”
Section: Stem Cell and H2s Signalingmentioning
confidence: 99%